Bricolage: Theoretical and Contemporary Uses of the Concept in Entrepreneurship Studies - Saheed A. Gbadegeshin (RossiSmith Academic Publications, 2025)
It is essential to have mutual understanding of theories, because their theoretical and contemporary uses change over time. Thus, this paper examines theoretical and contemporary uses of Bricolage theory in entrepreneurship studies. In doing so, it reviews scholarly articles on the theory through a documentary analysis method. Its findings showed that Bricolage was used across different fields of study. The findings also showed that there are differences between original and contemporary uses of the theory. Similarly, there is change in contextual meaning of the theory. Furthermore, it was noted that the theory was applied to different entrepreneurial phenomena, except certain contexts like entrepreneurial process, entrepreneurship education, and digitalization. This paper makes theoretical contribution by outlining key assumptions of Bricolage and its contextual meanings. It also provides insight for scholars and areas for further research.